N-Acetylmuramic Acid (MurNAc) Auxotrophy of the Oral Pathogen Tannerella forsythia: Characterization of a MurNAc Kinase and Analysis of Its Role in Cell Wall Metabolism - Hottmann, Isabel; Mayer, Valentina M. T.; Tomek, Markus B.; Friedrich, Valentin; Calvert, Matthew B.; Titz, Alexander; Schäffer, Christina; Mayer, Christoph (Frontiers in Microbiology, 2018)
Tannerella forsythia is an anaerobic, Gram-negative oral pathogen that thrives in multispecies oral biofilms associated with periodontitis. The bacterium is auxotrophic for the commonly essential bacterial cell wall sugar N‑acetylmuramic acid (MurNAc) and, thus, strictly depends on an exogenous supply of MurNAc for growth and maintenance of cell morphology. A MurNAc transporter (Tf_MurT; Tanf_08375) and an ortholog of the Escherichia coli etherase MurQ (Tf_MurQ; Tanf_08385) converting MurNAc-6-phosphate to GlcNAc-6-phosphate were recently described for T. forsythia. In between the respective genes on the T. forsythia genome, a putative kinase gene is located. In this study, the putative kinase (Tf_MurK; Tanf_08380) was produced as a recombinant protein and biochemically characterized. Kinetic studies revealed Tf_MurK to be a 6-kinase with stringent substrate specificity for MurNAc exhibiting a 6 x 104-fold higher catalytic efficiency (kcat/Km) for MurNAc than for N‑acetylglucosamine (GlcNAc) with kcat values of 10.5 s-1 and 0.1 s-1 and Km values of 200 µM and 116 mM, respectively. The enzyme kinetic data suggests that Tf_MurK is subject to substrate inhibition (Ki[S] = 4.2 mM). To assess the role of Tf_MurK in the cell wall metabolism of T. forsythia, a kinase deletion mutant (∆Tf_murK::erm) was constructed. This mutant accumulated MurNAc intracellularly in the exponential phase, indicating the capability to take up MurNAc, but inability to catabolize MurNAc. In the stationary phase, the MurNAc level was reduced in the mutant, while the level of the peptidoglycan precursor UDP-MurNAc-pentapeptide was highly elevated. Further, according to scanning electron microscopy evidence, the ∆Tf_murK::erm mutant was more tolerant towards low MurNAc concentration in the medium (below 0.5 µg/ml) before transition from healthy, rod-shaped to fusiform cells occurred, while the parent strain required >1 µg/ml MurNAc for optimal growth. These data suggest that T. forsythia readily catabolizes exogenous MurNAc but simultaneously channels a proportion of the sugar into peptidoglycan biosynthesis. Deletion of Tf_MurK blocks MurNAc catabolism and allows the direction of MurNAc solely to peptidoglycan biosynthesis, resulting in a growth advantage in MurNAc-depleted medium. This work increases our understanding of the T. forsythia cell wall metabolism and may pave new routes for lead finding in the treatment of periodontitis.